(3GdGbJUGO GdSjGSj ddYhdeIs - (3hhOR(B, (3fLjQs ((3GdbGgQIs (3GdeLdS GdGYdj ddKbGaIs, 2004)
(3aj gPG GdcJGH (B: 1 ) (3GdGbJUGO GdSjGSj ddYhdeI, fLjQ hhOR (B2) (3GdYhdeI hGdLZQGajG GdLOjOI ddGSJKeGQ GdCLfHj GdeHGTQ, Lhf CJT OGffL (B3) (3GdJLGQI hGdfRYI GdEbdjejI hGdNWQ GdPj jgOO JYOOjI GdCWQGa, OjGfG JhSj hfLjQ hhOR (B4) (3GdfbO aj YGde eYhde, HfLGejf Lj chjf (B5) (3gd JfceT GdOhd, LjaQj LGQjJ (B6) (3GdYhdeI HGYJHGQgG feW JacjQ aj GdcjGfGJ GdeDSSjI GdaGYdI GdcHQi, JheGS Ljg HjQSJjcQ (B7) (3GdeLJeY GdeOfj Gdchfj, LGf BQJ ThdJ (B8) (3GdJMOj GdPj JhGLgg GdeDSSGJ GdOhdjI, fLjQ hhORs
Keywords: (3GdGbJUGO GdSjGSjs; (3GdJfejI GdGbJUGOjIs; (3GdYhdeIs